Health care issues: A risk for fatal crashes amongst heavy vehicle drivers in oil and gas industry - Sabir, A.A. (American Scientific Publishers, 2017)
The oil and gas industry has an active role in the development of Malaysian economy. Oil and gas industry outpouring of products all depends on heavy vehicles transportation. The oil and gas transportation is a very sensitive issue for heavy vehicle drivers from centralized plants to the end users. According to the Malaysian Institute of Road Safety Research (MIROS), there are record fatalities and accidents among heavy vehicle drivers. This is a major health care issue for this industry. This study aims at assessing the health care issues such as; obesity, seat interface and back pain problems, on demographic characteristics; age, education and race among oil and gas truck drivers in Malaysia. The study based on in-depth literature review to find out the drivers health care issues that leads to fatal crashes. According to the best knowledge of the researcher, very rare studies have found out the health care's issues in context of Malaysian oil and gas Industry. This study also put emphasis on literature on safety training interventions in abating fatal crashes among truck drivers. Copyright © 2017 American Scientific Publishers All rights reserved.